Managing nuisance social insects in urban environments: an overview - Dimarco, Romina Daniela (2017)
Urbanization is progressing worldwide where social insects often attain pest status. We present an overview of the practices applied for the management of social insects in urban settings from 1990 to 2016. We found that most studies focus on the management and/or control of the colony via chemical means, many approaches based on controlling individual workers have been tried with less success than colony-level treatments, and only few used an integrated pest management approach. Less common is undertaking the reduction of populations through the control of the worker caste, by taking advantage of the Allee effects. This is an approach that could be further explored for sustainable control of social insects.